Liberatory ethics, education, paedeia and democracy. Experiences of the U.S. educational system - Sargis, John, (Universidad Nacional de Quilmes, 2004)
The liberatory effect of democratic ethics, following the introduction of the institutions of an inclusive democracy, is the necessary condition for paedeia. In turn, Paedeia is the sufficient condition for the development of a self-questioning democratic consciousness of autonomous individuals. There are few thinking people who would deny today that the educational system in the United States of America is broken. Its failures are variously attributed to the shortcomings of its teachers, its students (and their parents), or its administrators. It may be contended, however, that the system is fundamentally flawed; that its purpose is not, as common belief has it, to educate and to enlighten, and thereby to produce citizens who act in both their own and in their society's best interests, in other words, citizens for a true democracy. In fact, viewed historically and conceptually, the purpose of this educational system is to produce a mass work force, one which does not think for itself, but should accept without question the rhetoric of the economic and social elite, in other words the ruling class. What is needed is to reappropriate a term used in the ancient Greek world, paedeia; that is, a vision of education through which a society becomes democratic and just i.e. free from domination. This justice has therefore little to do with liberal or social democratic definitions of it, as a granting of a certain fairness and political rights fought for within the institutional framework of the market economy and representative democracy. In other words, ;justice here implies economic, social, ecological, and political autonomy and freedom.